PIONEER: Pipeline for Generating High‐Quality Spectral Libraries for DIA‐MS Data. Issue 3 (3rd March 2021) - Manda, Srikanth S.; Noor, Zainab; Hains, Peter G.; Zhong, Qing
Abstract: Data‐independent‐acquisition mass spectrometry (DIA‐MS) is a state‐of‐the‐art proteomic technique for high‐throughput identification and quantification of peptides and proteins. Interpretation of DIA‐MS data relies on the use of a spectral library, which is optimally created from data acquired from the same samples in data‐dependent acquisition (DDA) mode. As DIA‐MS quantification relies on the spectral libraries, having a high‐quality, non‐redundant, and comprehensive spectral library is essential. This article describes the major steps for creating a high‐quality spectral library using a combination of multiple complementary search engines. We discuss appropriate strategies to control the false discovery rate for the final spectral library as a result of merging multiple searches. © 2021 The Authors Current Protocols © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Searching DDA‐MS files with multiple search engines Basic Protocol 2 : Merging results from multiple search engines Basic Protocol 3 : Creating spectral libraries from merged results Alternate Protocol : Using CLI for automating tasks Support Protocol : Creating concatenated FASTA files